Direct calculation of incoherent phase diagrams by monte carlo simulation - 임상호; G. E. Murch; W. A. Oates (TAYLOR & FRANCIS, 1988)
A new Monte Carlo method which permits the direct calculation of incoherent phase diagrams is presented. The method involves maintaining each lattice quite separately during the calculation and determining the phase boundaries by equating both the chemical potential and the pressure between phases. The results of several calculations are presented as examples. This new simulation procedure may be applied to any type of incoherent phase diagram without the complication of metastability. ？ 1988 Taylor & Francis Group, LLC.